CENTRAL SEROUS CHORIORETINOPATHY TREATED WITH MINERALOCORTICOID ANTAGONISTS: A ONE-YEAR PILOT STUDY. Issue 3 (March 2016) - Ghadiali, Quraish; Jung, Jesse J.; Yu, Suqin; Patel, Samir N.; Yannuzzi, Lawrence A.
Abstract : Purpose: To assess the treatment response to mineralocorticoid antagonists in a pilot study of patients diagnosed with central serous chorioretinopathy using multimodal imaging. Methods: This retrospective observational case series included 23 eyes of 14 patients with central serous chorioretinopathy treated by a single physician (L.A.Y.) with either spironolactone, eplerenone, or both consecutively over a 12-month period. Choroidal thickness, central macular thickness, and best-corrected visual acuity were measured and compared with baseline values. Twelve eyes of 11 patients demonstrated subretinal fluid before or during the initiated treatment course. Subretinal fluid was measured and compared with baseline values in this subgroup. Results: In all eyes (n = 23), best-corrected visual acuity improved at 12 months of treatment; however, central macular thickness and choroidal thickness showed no improvement. In the subgroup with subretinal fluid (n = 12), subretinal fluid was significantly decreased at 6 months and 12 months of treatment; however, central macular thickness, choroidal thickness, and best-corrected visual acuity showed no significant change. Conclusion: Mineralocorticoid antagonists may improve best-corrected visual acuity and decrease subretinal fluid in patients with central serous chorioretinopathy, but do not affect the choroidal or macular thickness. This pilot study demonstrates that mineralocorticoid receptor antagonists may be effective in treating central serous chorioretinopathy but warrants consideration for future research within a randomized clinical trial. Abstract : When treated with mineralocorticoid antagonists, eyes with central serous chorioretinopathy demonstrated improvements in visual acuity and decreases in subretinal fluid; however, no sustained effects on choroidal or macular thickness were observed.